كفالة مبدأ الشرعية بين القانونين الجنائي الداخلي والدولي - دراجي, بلخير (جامعة الوادي - university of Eloued, 2017)
يعتبر مبدأ الشرعية ركنا هاما من أركان العقاب في مجال القانون الجنائي سواءا بالنسبة للدول التي تعتمد على القانون المكتوب أو الدول التي تأخذ بالقانون الغير مكتوب أو مايسمى بالشرعية العامة ، وهو مبدأ من المبادئ الرئيسية التي تقوم عليها الأنظمة الجنائية الحديثة . ووفقا لهذا المبدأ فهو يلزم وجود نص قانوني يحدد الجريمة وأنواعها من جهة ، ومبدأ الجزاء الجنائي والعقاب من جهة ثانية والذي يضفي هذا الوصف على ماديات معينة ،فينقلها من دائرة الإباحة إلى دائرة التجريم . The principle of legality is considered to be as o part of punishment parts in the field of the criminal law either for stotes that based on the written law or for states that based on the unwritten law or what is called general law which is one of the main principles re lying on the modern criminal systems. According to this principle that needs a legal text shows the crime and its types from a side and and the principle of the criminal punishment and punishment from the other side, this dexription may lend to specific materials that transfer it from the circle of permissibility to the circle prohibition.
مقال. المجلة الدولية للبحوث القانونية والسياسية . مج1. ع.1. جامعة الوادي
Keywords: قانون-دولي- جنائي-مبدأ الشرعية; the crime, principle of legality, modern criminal systems, the criminal law.